PEMANFAATAN TIKTOK SEBAGAI MEDIA KAMPANYE OLEH KUKUH HARYANTO SEBAGAI CALON LEGISLATIF DEWAN PERWAKILAN RAKYAT DAERAH KABUPATEN WONOGIRI DAPIL I TAHUN 2024 - Sari, Nanda Puspita; Riyanto, Buddy; Suryo Sardjono, Herning (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2024)
One manifestation of the development of communication technology is the birth of social media platforms, which have a significant impact, especially in the political realm. Kukuh Haryanto, Legislative Candidate for the Wonogiri Regency DPRD in 2024, is actively utilizing the TikTok social media platform to increase the intensity of his campaign among the public. The aim of this research is to describe the use of TikTok as a campaign media by Kukuh Haryanto as a legislative candidate for the Wonogiri Regency DPRD for electoral district I in 2024. The theory used in this research is the Mass Communication and Social Media theory of TikTok as New Media. This research uses a descriptive qualitative approach method by collecting data through interviews and documents. The research results show that Kukuh Haryanto's use of social media TikTok as a campaign tool in the legislative elections in Wonogiri Regency in 2024 is said to have not been effective in bringing legislative candidates closer to the voting public. TikTok is a platform that is used only to introduce oneself, build personal branding, disseminate information, and increase interaction with voters. However, political campaigns through this platform have proven to be less effective in forming political support, the votes obtained are not enough to usher in Kukuh Haryanto as a member of the Wonogiri Regency Regional People's Representative Council. Campaigns on TikTok tend to produce content that emphasizes entertainment aspects more than political substance. Keywords: Campaign, social media, TikTok